2008
DOI: 10.1518/001872008x354192
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Grip Force, Normal Force, Contact Area, Hand Size, and Handle Size for Cylindrical Handles

Abstract: The quantitative relationships described in this paper can be used in the design of objects and hand tools to determine optimal handle sizes for maximizing grip force, total normal force, or contact area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
93
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 15 publications
4
93
1
Order By: Relevance
“…Relative to what is known about how stone tool related behaviours may have influenced the evolution of human hand anatomy, however, a great deal less has been empirically demonstrated in respect to how biometric variation may have impacted on technological choices and cultural variability in the Lower Palaeolithic. The notion that individual biometric differences significantly influence hand-held tool use or gripping tasks is, however, both long lived and widely supported within engineering and ergonomic literature (e.g., Tichauer and Gage, 1977;Hall, 1997;Ruiz-Ruiz et al, 2002;Edgren et al, 2004;Nicolay and Walker, 2005;Hwang et al, 2011), with it having been demonstrated on a number of occasions that optimal tool forms are directly related to the biometric traits of tool users (e.g., Eksioglu, 2004;Seo and Armstrong, 2008). Such considerations indicate that those tool forms that are of greatest functional value, and thus the tool forms most likely to be replicated, are determined by the biometric conditions observed in a tool user's upper limb.…”
Section: Introductionmentioning
confidence: 99%
“…Relative to what is known about how stone tool related behaviours may have influenced the evolution of human hand anatomy, however, a great deal less has been empirically demonstrated in respect to how biometric variation may have impacted on technological choices and cultural variability in the Lower Palaeolithic. The notion that individual biometric differences significantly influence hand-held tool use or gripping tasks is, however, both long lived and widely supported within engineering and ergonomic literature (e.g., Tichauer and Gage, 1977;Hall, 1997;Ruiz-Ruiz et al, 2002;Edgren et al, 2004;Nicolay and Walker, 2005;Hwang et al, 2011), with it having been demonstrated on a number of occasions that optimal tool forms are directly related to the biometric traits of tool users (e.g., Eksioglu, 2004;Seo and Armstrong, 2008). Such considerations indicate that those tool forms that are of greatest functional value, and thus the tool forms most likely to be replicated, are determined by the biometric conditions observed in a tool user's upper limb.…”
Section: Introductionmentioning
confidence: 99%
“…The handle grip is improved by the optimum handle diameter in a way where it is easier to be secured in the hand and increases voluntary force applications. It is supported by other studies, where an optimal handle diameter increases the grip force and total normal force (Edgren et al, 2004;Kong and Lowe, 2005b;Mastalerz et al, 2009;Seo and Armstrong, 2008). At the same time, the secureness of the handle in the hand can be explained as the optimal handle diameter allowed the thumb and fingertips to work together against the palm, resulting in a greater reaction force (Seo and Armstrong, 2008).…”
Section: Effect Of Ergonomics Features On Handle Gripmentioning
confidence: 56%
“…At the same time, the secureness of the handle in the hand can be explained as the optimal handle diameter allowed the thumb and fingertips to work together against the palm, resulting in a greater reaction force (Seo and Armstrong, 2008). In addition, the grip force decreases along with the increase of the handle diameter beyond the optimal diameter (Edgren et al, 2004;Kong and Lowe, 2005b;Mastalerz et al, 2009;Seo and Armstrong, 2008).…”
Section: Effect Of Ergonomics Features On Handle Gripmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies have been carried out on grip force and the parameters that affect grip force, such as torque direction, object size and technique (Enders and Seo, 2011;Seo and Armstrong, 2008;Seo et al, 2008a;2008b). However, there appear to be no studies that investigate the effects of tactile sensation on pinch force.…”
Section: Introductionmentioning
confidence: 99%